The Relationship Between Atititudes In The Lecture Process And Student Learning Outcomes In The Pastry And Art Subjects S1 Culinary Arts UNP - Jessyca Putri Haminda; Asmar Yulastri (Universitas Negeri Padang, 2021)
This study aims to describe attitudes, describe learning outcomes and analyze the relationship between attitudes in the lecture process and student learning outcomes in the PastryAndArt S1 CulinaryArtUNP 2016 sessionA and sessionB. This type of research is descriptive correlational. The population and sources of research data are students who have completed the PastryAndArt S1 CulinaryArtUNP41 students of session A and session B were taken based on the saturated sampling technique. The data collection technique was made with a Likert scale and distributed research questionnaires through google forms which have been tested for validity and reliability. The data analysis technique was carried out by descriptive analysis, ideal data categorization methods, data analysis requirements test, correlation coefficient analysis and correlation coefficient significance analysis. The results of the overall attitude research of 41 respondents are known to be 1person(3%) in very high category, 28people (68%) in high category, 12people(29%) in moderate category, student learning outcomes of PastryAndArt S1 Culinary ArtUNP 2016 from 41 respondents in session A and session B as a whole very good category. SessionA(21 people) and sessionB(20 people) were 9people(42%) and 7people (35%); and the results of the study indicate that there is no significant relationship between attitudes in the lecture process and student learning outcomes in the PastryAndArt S1 CulinaryArtUNP 2016 course with a significant correlation coefficient value of 0.370> 0.05 so Ha is rejected and Ho is accepted.